Financial Sector Assessment : Moldova - World Bank (Washington, DC, 2013)
This Financial Sector Assessment (FSA) provides a summary of the main findings and recommendations of the work of the joint International Monetary Fund (IMF)-World Bank Financial Sector Assessment Program (FSAP) Update that visited Moldova from October 1 to 12, 2007. The principal objective of the FSAP Update was to assist the authorities in evaluating development progress and future challenges and assessing the potential vulnerabilities of the financial system in Moldova. In addition to the aide memoire summarizing key findings, the output included detailed assessments of compliance with the base core principles for banking supervision and the core principles for systemically important payment systems, technical notes on securities markets, the insurance sector, banking sector and stress testing.